The Scribble and Par complexes in polarity and migration: friends or foes? - Humbert, P.O.; Dow, L.E.; Russell, S.M. (Trends in Cell Biology, 2006)
The Par complex [consisting of Bazooka (also called Par3), Par6 and aPKC] is a well-described regulator of cell polarity whose role in many aspects of cell morphogenesis is under intense investigation. Recently, another set of proteins known as the Scribble complex (consisting of Scribble, Discs large and Lethal giant larvae) has also been shown to be important in polarity regulation in several settings. Here, we describe the current status of Scribble in polarity and review evidence from various model systems that indicates an essential but context-dependent role for the Scribble and Par complexes in directed cell migration. Based on the known interactions of Scribble and Par complexes with each other and with other signalling pathways, we propose models by which Par and Scribble might interact to regulate cell migration.